Isolation, Identification and Antimicrobial Activity of Marine Actinomycetes Isolated from Parangipettai - D. Stella, K. Sathiyaseelan* and (Recent Research in Science and Technology, 2011)
Five Actinomycetes strains were isolated from soil collected in two different regions of parangipattai. The physico-chemical characteristics of soil samples are analysed. Morphological studies indicated that the strains belonged to the genera Streptomyces spectabilis, Actinomadura roseale, Streptomyces platensis, Streptomyces kavamyceticus and Streptomyces citricolor. Out of five isolated Actinomycetes species, one was selected for antimicrobial activity against five human pathogens. Streptomyces citricolor showed the best level of antibacterial effect against Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae, Salmonella typhi and Vibrio cholerae whereas did not showed any antifungal effect against Aspergillus niger, Fusarium oxysporum,Rhizoctonia solani, Candida albicans and Penicillium citrinum.